2019
DOI: 10.5946/ce.2019.047
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for Colitis-Associated Dysplasia

Abstract: Dysplasia is a precancerous lesion of colorectal cancer in patients with long-standing inflammatory bowel diseases (IBDs), such as ulcerative colitis and Crohn’s disease. Recent guidelines suggest endoscopic resection as a key modality for the treatment of endoscopically resectable dysplasia in patients with colitis. Endoscopic submucosal dissection (ESD) has been suggested as one of the therapeutic options for dysplasia that is potentially resectable but not suitable for the conventional endoscopic mucosal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
12
0
1
Order By: Relevance
“…When we undertake piecemeal resections during EMR, we carefully evaluate the stump of the ulcer, and additional mucosal cautery trimming is performed, where necessary, which may reduce the risk of local recurrence. While local recurrence (0%–22.2%) and R0 resection rates (77%–80%) have been reported following ESD of tumors in patients with UC, 9,11,12,21,30 our lower local recurrence rate corresponded with a higher R0 resection rate (97%) compared with those reported previously.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…When we undertake piecemeal resections during EMR, we carefully evaluate the stump of the ulcer, and additional mucosal cautery trimming is performed, where necessary, which may reduce the risk of local recurrence. While local recurrence (0%–22.2%) and R0 resection rates (77%–80%) have been reported following ESD of tumors in patients with UC, 9,11,12,21,30 our lower local recurrence rate corresponded with a higher R0 resection rate (97%) compared with those reported previously.…”
Section: Discussionsupporting
confidence: 43%
“…In this study, we found that ESD was more effective than EMR with respect to the overall R0 and curative resection rates for tumors in patients with UC, despite the presence of significantly larger and more non‐polypoid lesions in the ESD group. Previous studies' findings have shown that the en bloc and R0 resection rates for ESD in patients with UC were 80–100% and 76–80%, respectively, 9–12,21 for tumors with median sizes of 15–33 mm, of which approximately 80% had non‐polypoid morphologies. Our results were similar to these findings, and they supported the feasibility of ESD for tumors that are difficult to be treated using EMR in patients with UC.…”
Section: Discussionmentioning
confidence: 97%
“…3 shows that the techniques and equipment used for en- www.irjournal.org doscopic submucosal dissection (ESD) for sporadic colorectal neoplasia is also applicable to UC-associated dysplasia. 29 To make this possible, the endoscopic specialist must be highly trained in colorectal ESD, taking into account the lesions and the current condition of the IBD patients. In this section, we introduce and summarize the molecular pathobiology of CAC, the current guidelines, and the latest international consensus statement for detection and management of CAC.…”
Section: Early Detection Of Colonic Neoplasia Using Molecular Imagingmentioning
confidence: 99%
“…Fig. 3 shows that the techniques and equipment used for endoscopic submucosal dissection (ESD) for sporadic colorectal neoplasia is also applicable to ulcerative colitis (UC)-associated dysplasia [ 29 ]. To make this possible, the endoscopic specialist must be highly trained in colorectal ESD, taking into account the lesions and the current condition of the IBD patients.…”
Section: Early Detection Of Colitis-associated Cancer In Ibdmentioning
confidence: 99%
See 1 more Smart Citation